2016
DOI: 10.1212/wnl.0000000000003028
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric multiple sclerosis

Abstract: Multiple sclerosis (MS) in children manifests with a relapsing-remitting MS (RRMS) disease course. Acute relapses consist of new neurologic deficits persisting greater than 24 hours, in the absence of intercurrent illness, and occur with a higher frequency early in the disease as compared to adult-onset RRMS. Most pediatric patients with MS recover well from these early relapses, and cumulative physical disability is rare in the first 10 years of disease. Brainstem attacks, poor recovery from a single attack, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 42 publications
4
54
1
4
Order By: Relevance
“…Heterogeneity in age at onset, disease course (monophasic versus relapsing), therapies utilized, clinical course, pathology and antibody titers in MOGAD patients in this study is consistent with the literature on MOGAD [34], but clear differences remain from MS and AQP4-IgG-seropositive NMOSD that suggest MOGAD is a distinct entity. The wide range in age of onset of MOGAD is similar to what is observed in other defined subsets of CNS inflammatory demyelinating diseases (both MS and aquaporin-4-IgG seropositive NMOSD can impact children or the elderly) [60,73,74]. There are however unequivocal major differences between MOGAD and MS in presenting manifestations (ADEM is common in MOGAD but very rare in MS), clinical course (a progressive course is not reported with MOGAD but the majority of MS patients eventually develop a progressive course) [30], frequency of CSF oligoclonal bands (8% of MOGAD in our study [similar to prior reports] [15,34] versus MS where it occurs in 88%) [14], and there are a number of MRI differences in the spinal cord, brain and optic nerve that have been reported [7,15,33].…”
Section: Discussionsupporting
confidence: 70%
“…Heterogeneity in age at onset, disease course (monophasic versus relapsing), therapies utilized, clinical course, pathology and antibody titers in MOGAD patients in this study is consistent with the literature on MOGAD [34], but clear differences remain from MS and AQP4-IgG-seropositive NMOSD that suggest MOGAD is a distinct entity. The wide range in age of onset of MOGAD is similar to what is observed in other defined subsets of CNS inflammatory demyelinating diseases (both MS and aquaporin-4-IgG seropositive NMOSD can impact children or the elderly) [60,73,74]. There are however unequivocal major differences between MOGAD and MS in presenting manifestations (ADEM is common in MOGAD but very rare in MS), clinical course (a progressive course is not reported with MOGAD but the majority of MS patients eventually develop a progressive course) [30], frequency of CSF oligoclonal bands (8% of MOGAD in our study [similar to prior reports] [15,34] versus MS where it occurs in 88%) [14], and there are a number of MRI differences in the spinal cord, brain and optic nerve that have been reported [7,15,33].…”
Section: Discussionsupporting
confidence: 70%
“…In children with a progressive course, other diagnoses should be considered. Children have been reported to have a higher relapse rate compared to adult-onset MS, especially within the first few years of diagnosis [31,32]. Studies have reported 2.3-2.8 times higher relapse rate in pediatric MS, and higher rates of relapse early in the disease if without treatment or on lower efficacy treatment [32][33][34].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…It is shown that children with MS tend to have a more inflammatory disease course than adults. 16 , 17 Therefore, we hypothesised that the predictive value of sCD27 levels for a second attack of MS will be equal or even higher in children than in adults. Furthermore, ADS with encephalopathy (ADEM) are known to have extensive intracerebral inflammation on magnetic resonance imaging (MRI) scans and may have severe clinical presentations.…”
Section: Introductionmentioning
confidence: 99%